Identitas Gender Tandhak dalam Pertunjukan â€œLudruk Suromenggolo Ponorogoâ€ - Qulud Dwitika Kusuma; Wahyu Novianto (Syntax Idea)
Ludruk Suromenggoloâ€™s tandhak performance as a woman character is not only displayed on stage but is carried over into her daily life. This is the cause of the loss of feminine and masculine spatial boundaries, thus blurring their true gender identities. The purpose of this study is to look at the form of performance presentation, the role of tandhak in the performance, and the process of forming gender identity tandhak on the stage of the Ludruk Suromenggolo performance. This study used the descriptive-qualitative method. Source of data obtained from primary and secondary data observational data collection techniques, interviews, and documentation. Data analisys uses triangulation with the stages of data reduction, data presentation, and drawing conclusions. Ludrukâ€™s performance structure theory and gender identity theory are used as a basis. The research result obtained show that tandhak created his role on stage through a series of make-up, costumes, self-discipline, speech, and behaviour. From this role, tandhak build their gender identity as feminine. The gender identity is formed from a social construction (gender role identity), which then becomes stronger because, from an early age, signs reveal their gender. The constancy of gender identity makes tandhak experience alienation and discrimination. Tandhak is recognised for its existence, but in the socio-political space, it is removed.